2009
DOI: 10.1007/s11064-009-0085-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Sulfide on Cyclic AMP Production in Isolated Bovine and Porcine Neural Retinae

Abstract: Hydrogen sulfide (H(2)S) has been reported to exert pharmacological effects on neural and non-neural tissues from several mammalian species. In the present study, we examined the role of the intracellular messenger, cyclic AMP in retinal response to H(2)S donors, sodium hydrosulfide (NaHS) and sodium sulfide (Na(2)S) in cows and pigs. Isolated bovine and porcine neural retinae were incubated in oxygenated Krebs buffer solution prior to exposure to varying concentrations of NaHS, Na(2)S or the diterpene activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…15 There is evidence that H 2 S donors can increase cyclic AMP production in isolated bovine and porcine retinae and retinal pigment epithelial cells, an effect that was dependent on endogenous biosynthesis of H 2 S and on the functional integrity of K ATP channels. 16,17 Taken together, these observations affirm the fact that H 2 S can have both physiological and pharmacological actions on ocular tissues.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…15 There is evidence that H 2 S donors can increase cyclic AMP production in isolated bovine and porcine retinae and retinal pigment epithelial cells, an effect that was dependent on endogenous biosynthesis of H 2 S and on the functional integrity of K ATP channels. 16,17 Taken together, these observations affirm the fact that H 2 S can have both physiological and pharmacological actions on ocular tissues.…”
Section: Introductionsupporting
confidence: 67%
“…For instance, H 2 S can alter neurotransmitter release from tissues of the anterior uvea and retina and can exert a neuroprotective action in the retina. 10,[15][16][17]19,27,28 There is evidence that H 2 S can relax both isolated mammalian irides and posterior ciliary arteries.…”
Section: Hydrogen Sulfide and Intraocular Pressure 373mentioning
confidence: 99%
“…Moreover the functional trans-sulfuration pathway in the retina proposes a protective action of this gas in this tissue. Studies from our laboratory have shown that H 2 S (using NaHS and Na 2 S as donors) can exert pharmacological effects in mammalian ocular tissues [23][24][25][26][27]. Although the enzymes involved in the biosynthesis of H 2 S are present in the eye, it is unclear whether they can generate this gas in situ.…”
Section: Discussionmentioning
confidence: 99%
“…In the eye, deficiency of CBS is often associated with many eye disorders including retinal degeneration, retinal detachment, optical atrophy and glaucoma [21,22]. Evidence from our laboratory have shown that H 2 S (using sodium hydrosulfide, NaHS and sodium sulfide, Na 2 S as donors) can relax ocular smooth muscle, regulate signal transduction processes and alter sympathetic and glutamergic neurotransmission in the anterior uvea and retina, an effect that is dependent on intramural biosynthesis of this gas [23][24][25][26][27]. Although enzymes involved in the biosynthesis of H 2 S are present in the eye and appear to be involved in mediating its pharmacological effects, to the best of our knowledge there are no reports of the basal levels of H 2 S in ocular tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In the posterior segment of the eye, it regulates cyclic adenosine monophosphate (cAMP) production and prejunctional excitatory neurotransmission in porcine and bovine retina (26). Moreover, ACS67, an H 2 S-releasing molecule, demonstrated a significant ocular hypotensive activity in glaucomatous rabbits and an elevation of reduced glutathione levels (27) which suggest a potential therapeutic application for H 2 S donors in ocular hypertension and neuropathies.…”
Section: Introductionmentioning
confidence: 99%